Towards an agenda of agricultural research in Europe - Boekestein, A.; Diederen, P.; Jongen, W.M.F.; Rabbinge, R.; Rutten, H. (Biology - Book Archive 2000-2006., 2000)
Directors of research, leaders of the public debate, government officials and scientific experts give their view on the future of agricultural research. The priorities for the next decades in the 21st century are discussed. Agriculture and consequently agricultural research are now localised in a much broader perspective. The focus is on Europe but the interaction with the other parts of the world is taken into account.Towards an Agenda for Agricultural Research in Europe gives a valuable overview of what is going on in Europe with regard to foresight studies and topics like sustainable development, consumer-orientation, safety and quality of food, environmental issues, non-food agroproduction, land use, the potential of biotechnology and new ways of structuring and steering of agricultural research. This book is indispensable in the next coming years as a guide for all those involved in policy and decision-making for agricultural research and agriculture.